A Multicenter Retrospective Study of 58 Patients With Primary Thyroid Diffuse Large B Cell Lymphoma - Yi, Jianing; Yi, Pingyong; Wang, Wei; Wang, Huan; Wang, Xinyu; Luo, Hanjia; Fan, Peizhi (Frontiers in Endocrinology, 2020)
BACKGROUND: Primary thyroid diffuse large B cell lymphoma (DLBCL) is a rare type of extranodal lymphoma, optimal treatment methods and the key prognostic factors have not been established. METHODS: The clinical data of 58 patients with primary thyroid DLBCL from January 2007 to December 2017 were collected. Kaplan–Meier method and log-rank tests were used for the survival analysis. The Cox regression analysis was performed to evaluate the prognostic factors. RESULTS: The follow-up time was 6–120 months, 5-year Overall survival (OS) and Progression Free Survival (PFS) were 73% and 61% respectively. Single factor analysis showed that IPI, Ki-67, treatment modalities, Hans classification, Myc/Bcl-2 protein coexpression and administration of rituximab had significant effect on the 5-year OS and PFS (P<0.05); while age, sex, Bcl-2 protein expression, Myc protein expression, tumor stage, tumor size, Hashimoto’s thyroiditis and B symptoms were not associated with prognosis (P>0.05). multivariate risk regression analysis revealed that Myc/Bcl-2 protein coexpression, treatment modalities, and Rituximab were independent prognostic factors (P<0.05). CONCLUSIONS: Patients with primary thyroid DLBCL who received combination chemotherapy with Radiotherapy had a better prognosis. Surgical treatment alone was not associated with the prognosis and is used only for diagnosis. Rituximab could improve the survival time of patients.